Effects of low level laser therapy on mucositis in patients under chemotherapy and bone marrow transplantation - Tavakoli, Azad; Tabarraee, Mahdi; Tabeie, Faraj; Mehdizadeh, Mahshid; Ghadiani, Mojtaba; Izadi Masoole, Leila (Novelty in Biomedicine, 2020)
Background: Oral mucositis is among the most important adverse effects of chemotherapy and bone marrow transplantation and prevention from this side effect is important to improve the situations in patients. Hence, in this study the main aim was to determine the effects of low-level laser therapy on mucositis in patients under chemotherapy and bone marrow transplantation. Materials and Methods: In this randomized controlled clinical trial, 60 consecutive patients under chemotherapy and bone marrow transplantation in a training hospital in 2018 were enrolled and randomly assigned to receive either low-level laser therapy (630 and 780 nm) or off-laser. Finally, the frequency rate and severity of mucositis (grades 0 to 4 according to WHO severity index) were determined and compared across the groups. Results: Mucositis was present in 30% and 56.7% in laser and control groups, respectively with statistically significant difference (p=0.037). The severity of mucositis was same across the laser and control groups (p=0.785). Conclusion: Low-level laser therapy is an effective modality for preventing from mucositis in patients treated by chemotherapy and bone marrow transplantation. Accordingly, utilization of this safe and effective therapeutic method is recommended.